Cookstoves illustrate the need for a comprehensive carbon market. (25th August 2015) - Sanford, Luke; Burney, Jennifer
Abstract: Existing carbon offset protocols for improved cookstoves do not require emissions testing. They are based only on estimated reductions in the use of non-renewable biomass generated by a given stove, and use simplistic calculations to convert those fuel savings to imputed emissions of carbon dioxide (CO2 ). Yet recent research has shown that different cookstoves vary tremendously in their combustion quality, and thus in their emissions profiles of both CO2 and other products of incomplete combustion. Given the high global warming potential of some of these non-CO2 emissions, offset protocols that do not account for combustion quality may thus not be assigning either appropriate absolute or relative climate values to different technologies. We use statistical resampling of recent emissions studies to estimate the actual radiative forcing impacts of traditional and improved cookstoves. We compare the carbon offsets generated by protocols in the four carbon markets that currently accept cookstove offsets (Clean Development Mechanism, American Carbon Registry, Verified Carbon Standard, and Gold Standard) to a theoretical protocol that also accounts for emissions of carbonaceous aerosols and carbon monoxide, using appropriate statistical techniques to estimate emissions factor distributions from the literature. We show that current protocols underestimate the climate value of many improved cookstoves and fail to distinguish between (i.e., assign equal offset values to) technologies with very different climate impacts. We find that a comprehensive carbon accounting standard would generate significantly higher offsets for some improved cookstove classes than those generated by current protocols, and would create much larger separation between different cookstove classes. Finally, we provide compelling evidence for the inclusion of renewable biomass into current protocols, and propose guidelines for the statistics needed in future emissions tests in order to accurately estimate the climate impact (and thus offsets generated by) cookstoves and other household energy technologies.